PENINGKATAN KEMAMPUAN MENGAJAR GURU BINAAN MELALUI SUPERVISI KUNJUNGAN KELAS DENGAN TEKNIK OBSERVASI KELAS SECARA LANGSUNG DI SD NEGERI 90 BENGKULU SELATAN - Supranuddin Supranuddin (PAKAR Pendidikan, 2015)
The main discussion in this school’s action research is the supervisory teachers through classroom visits supervision with direct observation technique class in particular aspects of learning process of planning and implementation of Teaching and Learning Process (PBM) in the classroom to improve the ability of teachers teaching in Elementary School 90 South Bengkulu. The objective of this school action research (PTS) is to (1) determine the readiness of the learning process planning; (2) assist the teacher in preparing the planning process so that the learning and teaching capabilities can be increased, and (3) determine the extent of supervision visits classes with direct classroom observation techniques on the ability of teachers to teach in an attempt to improve the learning quality in Elementary School 90 South Bengkulu. The results at the end of the cycle to the results of the pre-coaching and coaching study lesson plan for an average value of all research subjects obtained were classified as good (74.3) according to the standard process. Of all research subjects, the results of the post-mentoring and coaching study lessons plan were classified as good (82.5) according to the standard process, while the results of the teachers’ teaching ability in the implementation of the learning process were categorized well (81) according to the standard process. It can be concluded that the form of supervision visits classes with direct classroom observation techniques can improve the ability of teachers to teach in Elementary School 90 South Bengkulu.